Write like a man: Jewish masculinity and the New York intellectuals - Grinberg, Ronnie A. (Princeton University Press, 2024)
"In the years following World War II, the New York intellectuals became some of the most renowned critics and writers in the country. Although mostly male and Jewish, this prominent group also included women and non-Jews. Yet all of its members embraced a secular Jewish machismo that became a defining characteristic of the contemporary experience. Write like a Man examines how the New York intellectuals shared a uniquely American conception of Jewish masculinity that prized verbal confrontation, polemical aggression, and an unflinching style of argumentation. Ronnie Grinberg paints illuminating portraits of figures such as Norman Mailer, Hannah Arendt, Lionel and Diana Trilling, Mary McCarthy, Norman Podhoretz, Midge Decter, and Irving Howe. She describes how their construction of Jewish masculinity helped to propel the American Jew from outsider to insider even as they clashed over its meaning in a deeply anxious project of self-definition. Along the way, Grinberg sheds light on their fraught encounters with the most contentious issues and ideas of the day, from student radicalism and the civil rights movement to feminism, Freudianism, and neoconservatism."--